A Critical literature review of digital transformation and governance for competitive advantage - Made Yudi Darmita; Ida Bagus Raka Suardana; A.A Eddy Supriyadinata Gorda; Ida Ayu Oka Martini (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Cooperatives face persistent performance challenges amid accelerating digital disruption and governance demands; this study critically examines how digital transformation and Good Cooperative Governance (GCG) function as strategic resources shaping competitive advantage and cooperative performance. Using a Critical Literature Review (CLR) of peer-reviewed studies (2021–2025) sourced from Scopus, Google Scholar, and SINTA-indexed journals, 30 relevant journal articles were identified and critically analyzed to synthesize theoretical perspectives, conceptual frameworks, and empirical findings related to digital capabilities, governance, competitive advantage, and multidimensional performance. The review finds that digital transformation and GCG operate as interdependent organizational capabilities whose strategic value emerges when aligned; sustainable competitive advantage functions as the central mediating mechanism translating these capabilities into improved financial and nonfinancial outcomes such as member satisfaction, service quality, and long-term sustainability. However, the literature reveals conceptual ambiguities, inconsistent operationalizations of competitive advantage, limited attention to cooperative-specific governance dynamics, and a shortage of longitudinal and context-sensitive studies. We offer an integrative conceptual model that clarifies these relationships and propose a research agenda emphasizing cooperative-centric theorization, longitudinal and mixed-method designs, and adaptive governance practices to enable effective digital transition. Practitioners should prioritize governance alignment, capacity building, and member engagement to realize the strategic benefits of digital investments.